Monkey Pox Symptom Identification, Cause, Treatment and Infection Control Prevention - Vicia Dara Wandira; Rifki Adrian Syach (Journal of Basic Medical Veterinary)
Monkey pox is a zoonotic disease that is re-emerging and proliferating in areas where it has not been observed for decades. Monkey pox outbreaks have been documented periodically in the past. Significant outbreaks occurred in Nigeria during 2017-2018, as well as in the United States and Nigeria. The research method used was a literature evaluation, specifically covering literature collected from multiple sources relating to monkey pox disease. Monkey pox is caused by the monkey pox virus. The disease is endemic in Central and West Africa. Human cases have recently spread to additional locations. No cases of monkey pox have been reported in Indonesia. Monkey pox in humans has similarities to smallpox; however, the symptoms are usually less severe. The monkey pox virus is present in skin lesions and in throat and nasopharyngeal swabs. Monkey pox is self-limiting. Treatment is palliative. Transmission of the disease can be reduced by avoiding direct contact with wild animals. In conclusion, monkey pox is a zoonotic disease caused by the monkey pox virus. The disease is self-limiting. The treatment given is symptomatic. The recommended method to prevent transmission is to avoid contact with sick individuals or animals.